Answer:
The mistake is in step 2
Explanation:
We are given h(x)=4-x
Note: Considering h(x)=4-x as in question given there is some issue. If value of h(x) is different the answer would be different.
and g(x)=2x+10
We need to find h(g(x))
h(g(x)) can be found by putting the value of g(x) in h(x)
Steps used by Mario are:
Step 1: h(g(x)) = 4 - x
Step 2: h(g(x)) = 4 - x + 10
Step 3: h(g(x)) = 14 - X
She did mistake in step 2:
The step 2 should be:
h(g(x))=4-(2x+10)
h(g(x))= 4-2x-10
h(g(x))=-6-2x
So, the mistake is in step 2